Violence and media discourse: an integrative literature review (Brazilian Journal of Health Research, 2025)
Introduction: The relationship between media and violence reflects the power dynamics that permeate society. Media narratives often adopt a sensationalist approach to violence, highlighting extreme cases and perpetuating stigmas against certain social groups. Objective: To investigate how media narratives about violence impact the development of public policies in Brazil. Methods: An integrative literature review was conducted, with data collection between October and December 2024, using the SciELO and Virtual Health Library (BVS) databases. Articles published between 2014 and 2024 were selected. The search terms used were: "Media discourse," "Violence," "Public policies," combined with the Boolean operator "AND." Results: Twelve articles were included as the final sample, and their content was categorized into three thematic approaches: “Media narratives on violence,” “Impact on public policy development,” and “Responsible and ethical media coverage.” Conclusion: Media narratives about violence do not merely reflect reality but also shape public discourse and influence the formulation of public policies in Brazil. By emphasizing solutions aimed at social inclusion and the reduction of inequalities, the media can contribute to the adoption of more effective and humanized policies, promoting a fairer, safer, and less violent society.
Keywords: Media exposure; Violence; Public policy